Sustainability of Nigeria’s Rail Transport System: An Economic Perspective (International Journal of Scientific Research and Management (IJSRM), 2024)
The availability of an efficient transport system is germane in achieving trade promotion, social integration, business connectivity and economic development because transport plays relevant role in the growth of nation’s market. Some scholars have given undeniable linkages to the role of rail transport in economic development while there are deferring summations by some scholars hence this study explored the economic sustainability of Nigeria’s rail transport system to contribute to the body of knowledge debating the economic sustainability of rail transport globally. Previous researches have also been done in Nigeria and internationally on the subject area using different approaches but this research used concurrent triangulation design to validate the formulated hypothesis that rail transport system has not significantly affected local economic development. This was validated using simple linear regression and key informant interview (KII). The theoretical lens for the study is the Rostow’s stages of economic growth. The result, [R2= .12, F (1, 172) = 24.31, p < .01] showed that rail transport has contributed significantly to the local economic development and the KII generally reinforce the empirical findings hence hypothesis is rejected. This study recommended the permitting of more vendors providing services at the terminal as this will lead to vibrant local economic development whilst improving the standard of living of residents and the adoption of a holistic economic sustainability policy be embraced by the managers of rail transport system in the country.